Antecedents of behavioural intention of fraudulent financial reporting : Malaysian evidence / Siti Noor Hayati Mohamed Zawawi - Mohamed Zawawi, Siti Noor Hayati (2010)
The occurrence of fraudulent financial reporting is increasing and spreading despite various actions have been taken such as amending the Companies Act 1965, revising the Bursa Malaysia's listing requirements and revising the Malaysian Code on Corporate Governance. One of the reasons for the continuing trend may be that the problem is not addressed at the root level. The main aim of this study was to identify the root causes of fraudulent financial reporting behaviour. In particular, to examine whether the manager and executive's attitude toward behaviour, social pressure, perceived behavioural control and religiosity significantly influence his or her behavioural intention of fraudulent financial reporting. This study also investigates whether there are certain beliefs that influence the individual's attitude toward behaviour, social pressure and perceived behavioural control. The theory of planned behaviour was used as the theoretical framework for this study.